Scored Basins from Late Minoan Crete: an Experimental Interpretation from Construction to Functionality - Brianna Jenkins (EXARC Journal, 2022)
During the Bronze Age in Crete, agriculture, pottery production, metallurgy, textiles, architectural feats, trade, and other specializations flourished. Throughout habitation on Crete, pottery production was an area of craftsmanship and practicality from the end of the Neolithic to Mycenean and Iron Age. This experiment, however, relates to the Late Minoan I period in the geographical region of Mochlos. The Artisan’s Quarter is a building that contains various rooms that have been tied to craftsmanship and workshops. Once connected by a land bridge to the ancient site of Mochlos, this particular building would have been the place of vast amounts of pottery production. Activities would have ranged from the clay preparation to forming the vessels by hand or wheel to the decoration choices to the firing, and then finally to the exportation. For this experiment, the construction of the kiln was based on the research of two kilns of differing sizes and characteristics in this area, combined with other Late Minoan sites on Crete, to understand firing techniques and building aspects. Chalinomouri was another place of specialization. It was a small habitation that seemed to concentrate on agriculture. The pottery collected from this site varies in date and function, which is similar to that of the Artisan’s Quarter. As seen in the excavations at Mochlos, the scored basins were discovered fragmented within various rooms of different activities, suggesting their fabrication and possible function.